2021
DOI: 10.1007/jhep03(2021)298
|View full text |Cite
|
Sign up to set email alerts
|

Five-brane current algebras in type II string theories

Abstract: We study the current algebras of the NS5-branes, the Kaluza-Klein (KK) five-branes and the exotic $$ {5}_2^2 $$ 5 2 2 -branes in type IIA/IIB superstring theories. Their worldvolume theories are governed by the six-dimensional $$ \mathcal{N} $$ N = (2, 0) tensor and the $$ \mathcal{N} $$ N = (1, 1) vector multiplets. We show that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The last fact has been empirically observed (through direct calculations of Poisson brackets) in a number of works that discuss brane current algebras in phase space, starting with a relatively early paper by Bonelli and Zabzine that relates a p-brane current algebra to an algebroid involving T M ⊕Λ p T M [11], and more recently for M2, M5 and D-branes by Hatsuda and collaborators [12][13][14] and also by Sakatani and Uehara [15]. Our construction explains why O(d, d)-and E d(d) -covariant structures and (exceptional) Dorfman, Courant, Vinogradov .…”
Section: Jhep11(2021)114mentioning
confidence: 90%
“…The last fact has been empirically observed (through direct calculations of Poisson brackets) in a number of works that discuss brane current algebras in phase space, starting with a relatively early paper by Bonelli and Zabzine that relates a p-brane current algebra to an algebroid involving T M ⊕Λ p T M [11], and more recently for M2, M5 and D-branes by Hatsuda and collaborators [12][13][14] and also by Sakatani and Uehara [15]. Our construction explains why O(d, d)-and E d(d) -covariant structures and (exceptional) Dorfman, Courant, Vinogradov .…”
Section: Jhep11(2021)114mentioning
confidence: 90%
“…In F-theory the 5-brane represents the SL(5) U-duality symmetry [46]. Recently it was shown that current algebras of 5-branes are preserved under the S and T-duality transformations with renaming the spacetime coordinates, where 5-branes include the NS5-brane, the D5-brane, KK5-branes and exotic 5-branes in 32-supersymmetric string theories [54]. 5-brane may give a clue of duality web including 16 supersymmetric string theories.…”
Section: Jhep11(2021)201 6 Conclusionmentioning
confidence: 99%
“…The aim of this paper is to close that gap and propose an E d(d) -covariant Hamiltonian formulation of world-volume theories, building on previous attempts [50,64,65] and most recently [66]. Besides the typical objects of E d(d) generalised geometry an additional object, the above mentioned charge, that specifies the type of world-volume, needs to be introduced to ensure E d(d) -covariance.…”
Section: Introductionmentioning
confidence: 99%